Rapid screening of SARS-CoV-2 infection: Good performance of nasopharyngeal and Nasal Mid-Turbinate swab for antigen detection among symptomatic and asymptomatic individuals. - Paola Sicilia (PLoS ONE, 2022)
Although the nasopharyngeal swab (NPS) is considered the gold standard for the diagnosis of the SARS-CoV-2 infection, the Nasal Mid-Turbinate swab (NMTS) is often used due to its higher tolerance among patients. We compared the diagnostic performance of the NPS and the NMTS for the Panbio™ COVID-19 antigen-detecting rapid diagnostic test (Ag-RDT). Two hundred and forty-three individuals were swabbed three times by healthcare professionals: a NMTS and a NPS specimen for the Ag-RDT and an oropharyngeal swab for real time RT-PCR. Forty-nine participants were RNA-SARS-CoV-2 positive by real time RT-PCR: 45 and 40 were positive by the Ag-RDT with NPS and NMTS, respectively. The overall sensitivity and specificity were 91.8% (95% CI: 83.2-100.0) and 99.5% (95% CI: 98.2-100.0) for Ag-RDT with NPS, and 81.6% (95% CI: 69.8-93.5) and 100.0% (95% CI: 99.7-100.0) for the Ag-RDT with NMTS. The Cohen's kappa index was 0.92 (95% CI: 0.85-0.98). Among asymptomatic individuals, the Ag-RDT with both sampling techniques showed a high sensitivity [100.0% (95% CI: 95.5-100.0) with NPS; 90.9% (95% CI: 69.4-100.0) with NMTS], while the performance of the test decreased in samples with Ct≥ 30 and in patients tested after the first 7 days from symptom onset. Although the NMTS yielded a lower sensitivity compared to NPS, it might be considered a reliable alternative, as it presents greater adherence among patients, enabling scaling of antigen testing strategies, particularly in countries with under-resourced health systems.